Histone deacetylase 3 aberration inhibits Klotho transcription and promotes renal fibrosis - Chen, Fang (Cell Death Differ, 2020)
Development of renal fibrosis is a hallmark of renal aging and chronic kidney disease of all etiologies and characterized by extensive renal cell injuries and subsequent myofibroblast transdifferentiations (MTDs), which are significantly influenced by aberrant histone deacetylase (HDAC) activities. However, the key HDAC isoforms and effectors that are causally involved in the processes remain poorly understood. Here, we report that aberrant HDAC3 induction and its inhibition of Klotho, a renal epithelium-enriched aging suppressor, contribute significantly to renal fibrogenesis. HDAC3 was preferentially elevated with concomitant Klotho suppression in fibrotic kidneys incurred by unilateral ureter obstruction (UUO) and aristolochic acid nephropathy (AAN), whereas Hdac3 knockout resisted the fibrotic pathologies. The HDAC3 elevation is substantially blocked by the inhibitors of TGFβ receptor and Smad3 phosphorylation, suggesting that TGFβ/Smad signal activates Hdac3 transcription. Consistently, an HDAC3-selective inhibitor RGFP966 derepressed Klotho and mitigated the renal fibrotic injuries in both UUO and AAN mice. Further, HDAC3 overexpression or inhibition in renal epithelia inversely affected Klotho abundances and HDAC3 was inducibly associated with transcription regulators NCoR and NF-kB and bound to Klotho promoter in fibrotic kidney, supporting that aberrant HDAC3 targets and transcriptionally inhibits Klotho under renal fibrotic conditions. More importantly, the antirenal fibrosis effects of RGFP966 were largely compromised in mice with siRNA-mediated Klotho knockdown. Hence, HDAC3 aberration and the subsequent Klotho suppression constitute an important regulatory loop that promotes MTD and renal fibrosis and uses of HDAC3-selective inhibitors are potentially effective in treating renal fibrotic disorders.